Imunitas Negara dalam Kontrak Internasional: Analisis Jure Gestionis dalam Sengketa Kementerian Pertahanan RI vs. Navayo Internasional - Oktariani, Fely; Hibatullah, Muhamad Naufal (Nagari Law Review, 2025)
The increasing involvement of states in cross-border commercial activities has raised complex legal questions regarding the limits of sovereign immunity, especially when states engage in contractual relations with private entities. This article aims to analyse whether the contractual engagement of the Indonesian Ministry of Defense with Navayo International AG can be classified as a jure gestionis act, and how such classification affects the applicability of state immunity in international arbitration. Using a normative juridical method, this research applies a statute approach to examine national and international legal instruments, a conceptual approach to explore the doctrines of jure imperii and jure gestionis, and a case study approach focusing on the Navayo dispute alongside comparative jurisprudence. Primary legal materials such as conventions and arbitral awards, supported by secondary literature, are systematically analysed to clarify the boundary between sovereign and commercial acts. The study finds that the Ministry of Defense acted in a commercial capacity, thereby falling within the scope of jure gestionis, which excludes immunity from international arbitral jurisdiction. The conclusion emphasizes that Indonesia’s lack of specific legislation on state immunity creates legal uncertainty in the enforcement of arbitral awards. This article contributes to the discourse on the need for Indonesia to adopt restrictive immunity through comprehensive legislation to enhance legal certainty and strengthen its position in international business disputes.